Preconceito racial ou competição econômica? A opinião pública sobre a vinda de estrangeiros para o Brasil - Santos, Cíntia Soares Rodrigues dos (2021)
The master thesis discusses how Brazilian public opinion behaves in relation to foreigners coming to the country. Specifically, it tests two important theoretical approaches presente in the literature: racial prejudice and economic competition. The perception of the arrival of foreigners is measured using data from a survey prepared by SECOM/PR in 2015 and the analyzes suggest that both dimensions are present, although the evidence for the first is stronger, that is, the results point to the existence of a selectivity in the acceptance of foreigners considering their origin and race. When observing that foreigners of African or Haitian origin were perceived in a more negative way, they suggest the existence of racial and origin prejudice in the way in which some groups of immigrants are categorized and question the idea that foreigners are always welcome and well received in Brazil. The probability of negatively seeing the coming of foreigners to Brazil is greater when they come from countries with a predominantly black population, such as Haiti and countries in Africa, compared to other groups, such as Latinos, Asians, Europeans and Americans. This fact is supported by the historical and social construction of Brazil presented here. A history that is marked by a slavery and subjugation heritage of the black population.